The Analysis Of The Notary's Responsibilities For The Storage Of Electronic Deed Minuta - Wijayanti, Fika Arum; Santoso, Budi (Jurnal Hukum Volkgeist, 2023)
The role and authority of notaries who keep electronic minutes are often problematic. In practice, storing deed minutes electronically has obstacles and benefits. This research aims to determine and evaluate the process and obligations of Notaries in storing electronic deed minutes. The research methodology used is a sociological and legal research approach. Descriptive analysis is the analysis technique used in this research. Primary data used in this research includes the 1945 Constitution, Law No. 2 of 2014, the Mortgage Rights Law, the Civil Code, and the Criminal Code. Apart from that, secondary data such as books and supporting documents are also used. Research data was collected using interview techniques and studying documents or library materials. Research findings indicate that electronic deed minutes can be stored, as some laws allow it. To store deed minutes electronically, the minutes must be original and must be created and stored using conventional methods.